Elliptic curve‐based proxy re‐signcryption scheme for secure data storage on the cloud. (6th January 2020) - Patonico, Simone; Shabisha, Placide; Braeken, An; Touhafi, Abdellah; Steenhaut, Kris
Summary: Consider the situation of a patient carrying a body area network with sensors measuring different body characteristics. These data should be securely sent to the cloud and only retrievable by doctors authorized by the patient. Even the cloud service provider should not be able to derive the sensible data. In order to address this problem, this paper first proposes a highly efficient certificate‐based signcryption scheme, able to execute signing and encryption in one single phase and to guarantee the link between identity and public key. We show that our proposed scheme outperforms others both in computation and communication complexity. Next, based on this primitive, a complete proxy re‐signcryption scheme is presented to be integrated in this smart body area network. The proposed schemes are based on elliptic curve operations and do not use compute intensive pairing operations, like previous proposals. We show that our scheme outperforms previous proposed proxy re‐signcryption schemes in the literature.